A Colonized Islam: Pesantren, Resistance, and the Challenge of Religious Moderation in Indonesia - Haris Fatwa Dinal Maula (Journal of Religion and Decoloniality, 2025)
Decoloniality confronts the persistent colonial frameworks and narratives that continue to influence global perceptions, including religious activities. Colonial discourses have frequently mischaracterized Islam, portraying it as intolerant and violent. This colonial heritage has concealed the authentic nature of Islam, especially its potential for moderation and peace. The lack of religious moderation among certain Muslims, influenced by colonial conceptions, has resulted in actions that are antithetical to the fundamental principles of Islam.  In response, Islamic boarding schools (pesantren) in Indonesia have adopted educational frameworks that prioritize moderation and challenge colonial myths. Pesantren Bumi Cendekia in Yogyakarta employs the four academic pillars to cultivate a moderate and progressive comprehension of Islam among its pupils (santri). This method promotes religious moderation while simultaneously countering the colonial legacies that have influenced Islamic education. Bumi Cendekia encourages students to engage with many religious and cultural traditions through these four pillars, fostering an inclusive and decolonized perspective of Islam. This qualitative study, integrating fieldwork and literature evaluation, examines how Bumi Cendekia’s educational method represents a decolonial reaction to global religious discourses, enabling students to adopt a moderate, progressive, and global-engaged Islam.